Targeting DNA damage repair mechanisms in pancreas cancer - Perkhofer, Lukas; Golan, Talia; Cuyle, Pieter-Jan; Matysiak-Budnik, Tamara; Van Laethem, Jean-Luc; Macarulla, Teresa; Cauchin, Estelle; Kleger, Alexander; Beutel, Alica K.; Gout, Johann; Stenzinger, Albrecht; Van Cutsem, Eric; et al. (Cancers, 2021)
Impaired DNA damage repair (DDR) is increasingly recognised as a hallmark in pancreatic ductal adenocarcinoma (PDAC). It is estimated that around 14% of human PDACs harbour mutations in genes involved in DDR, including, amongst others, BRCA1/2, PALB2, ATM, MSH2, MSH6 and MLH1. Recently, DDR intervention by PARP inhibitor therapy has demonstrated effectiveness in germline BRCA1/2-mutated PDAC. Extending this outcome to the significant proportion of human PDACs with somatic or germline mutations in DDR genes beyond BRCA1/2 might be beneficial, but there is a lack of data, and consequently, no clear recommendations are provided in the field. Therefore, an expert panel was invited by the European Society of Digestive Oncology (ESDO) to assess the current knowledge and significance of DDR as a target in PDAC treatment. The aim of this virtual, international expert meeting was to elaborate a set of consensus recommendations on testing, diagnosis and treatment of PDAC patients with alterations in DDR pathways. Ahead of the meeting, experts completed a 27-question survey evaluating the key issues. The final recommendations herein should aid in facilitating clinical practice decisions on the management of DDR-deficient PDAC.